2000
DOI: 10.1016/s0002-9440(10)65024-9
|View full text |Cite
|
Sign up to set email alerts
|

The Indispensability of Heme Oxygenase-1 in Protecting against Acute Heme Protein-Induced Toxicity in Vivo

Abstract: Heme oxygenase (HO) is the rate limiting enzyme in the degradation of heme, and its isozyme, HO-1, may protect against tissue injury. One posited mechanism is the degradation of heme released from destabilized heme proteins. We demonstrate that HO-1 is a critical protectant against acute heme protein-induced toxicity in vivo. In the glycerol model of heme protein toxicity-one characterized by myolysis, hemolysis, and kidney damage-HO-1 is rapidly induced in the kidney of HO-1 ؉/؉ mice as the latter sustain mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
209
1
11

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(225 citation statements)
references
References 36 publications
4
209
1
11
Order By: Relevance
“…This effect is in agreement with results that have been described by others. Nath et al (2,41,42) showed that a decrease in HO activity predisposed rats to marked tubular interstitial inflammation and mortality after repetitive dosing with hemoglobin. It is also in agreement with those who have studied HO-2 deficiency in the heart and lung (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is in agreement with results that have been described by others. Nath et al (2,41,42) showed that a decrease in HO activity predisposed rats to marked tubular interstitial inflammation and mortality after repetitive dosing with hemoglobin. It is also in agreement with those who have studied HO-2 deficiency in the heart and lung (43).…”
Section: Discussionmentioning
confidence: 99%
“…These are attributed to the capacity of HO to degrade heme that is released from oxidant-destabilized heme proteins (2) and to the production of bilirubin, which has potent antioxidant effects (3), as well as the generation of the vasodilator gas carbon monoxide (CO) (1). HO-1 and HO-2, the inducible and constitutive HO forms, respectively, play an important role in maintaining renal blood flow (4).…”
mentioning
confidence: 99%
“…In complementary studies, the prior induction of HO-1 by "conditioning" the kidney by exposure to small amounts of hemoglobin (9), endotoxin (37), or nephrotoxic serum (38) also conferred protection against glycerol-induced acute renal failure, as did hyperbilirubinemia, the latter achieved by bile duct ligation (39). In addition, mutant mice that are unable to express HO-1 exhibit markedly increased sensitivity to heme proteins as evidenced by heightened renal injury, accumulation of heme, and increased mortality when subjected to the glycerol model or hemoglobin (40).…”
Section: Ho-1 As a Protectant Against Heme/heme Protein-induced Renalmentioning
confidence: 99%
“…Перша розглядається як стресовий протеїн, синтез якого індукується у відповідь на різні стрес-фактори та забезпечує захист клітин від ушкоджуючої дії вільного гему. Раніше встановлено важливість індукції ГО-1 за умови рабдоміолізу, стимульованого гліцерином [5]. Так, у нокаут-них по гену даного ізоферменту тварин на експериментальній моделі рабдоміолізу набувають розвитку симптоми ниркової недостатності зі 100%-ною летальністю.…”
Section: результати досліджень і їхнє обговоренняunclassified
“…Відомо, що індукція гемоксидази є одним із основних механізмів деградації гемопротеїнів та перешкоджає розвитку тканинних ушкоджень у нирках при рабдо-міолізі у щурів [2,4] та при ін'єкції гемоглобіну мишам [5]. У процесі інтенсивного вивільнення гему з цих протеїнів можливе утворення вільного феруму.…”
unclassified